Pendampingan dalam Pengolahan Nastar dari Nanas bagi Masyarakat Dukuh Barak 1 - Annafii, Argya Muhammad; Saputra, Naufal Ahmad; Pangestu, Bangun Yoga; Ghofari, Alfiga; Ramadhani, Noviana; Nani, Sri Marfah; Ardiyan, Muhammad Rizky; Shabella, Nita; Fathurrahman, Amar Ghifari; Azhari, Miftahurrizqi Putri; Febriani, Erma (Universitas Muhammadiyah Yogyakarta, 2025)
Community Service Program (KKN) is a community service program that aims to develop local potential and improve community welfare. Regular KKN Group 105 of Muhammadiyah University of Yogyakarta for the 2024/2025 period was implemented in Dukuh Barak 1, Margoluwih Village, Seyegan District, Sleman Regency, with the theme